2021
DOI: 10.3390/ijms22136865
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma and Metastasis Associated Bone Degradation—A Tale of Osteoclast and Malignant Cell Cooperativity

Abstract: Cancer-induced bone degradation is part of the pathological process associated with both primary bone cancers, such as osteosarcoma, and bone metastases originating from, e.g., breast, prostate, and colon carcinomas. Typically, this includes a cancer-dependent hijacking of processes also occurring during physiological bone remodeling, including osteoclast-mediated disruption of the inorganic bone component and collagenolysis. Extensive research has revealed the significance of osteoclast-mediated bone resorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 95 publications
0
38
0
Order By: Relevance
“…Osteosarcoma is associated with high rates of pulmonary metastasis [ 1 ]. The prognosis for patients with pulmonary metastasis is worse than for those with localized disease, characterized by substantially reduced survival [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteosarcoma is associated with high rates of pulmonary metastasis [ 1 ]. The prognosis for patients with pulmonary metastasis is worse than for those with localized disease, characterized by substantially reduced survival [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma, the most common primary bone malignancy, is renowned for its high propensity for metastasis [ 1 ]. As many as 20% of patients present with lung metastases at their initial diagnosis; around 40% of patients develop metastases after their initial presentation despite the best available treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, osteoclast bone resorption can lead to the release of pro-tumor factors as IGF-1 (Insulin Growth Factor 1) and TGF-β from the bone matrix that stimulate tumor cells [50,51]. The role of osteoclasts in the onset and progression of osteosarcoma is still controversial [52,53]. There are clinical and experimental data showing that the presence of osteoclasts in osteosarcoma-adjacent tissue is associated with poor outcomes [52], but on the other hand, published studies suggest that the presence of osteoclasts at the primary site of OS lesions prevents metastasis [52,54].…”
Section: Molecular Mechanisms Of Osteosarcoma Progressionmentioning
confidence: 99%
“…The role of osteoclasts in the onset and progression of osteosarcoma is still controversial [52,53]. There are clinical and experimental data showing that the presence of osteoclasts in osteosarcoma-adjacent tissue is associated with poor outcomes [52], but on the other hand, published studies suggest that the presence of osteoclasts at the primary site of OS lesions prevents metastasis [52,54]. Endo-Munoz et al found that expression of osteoclast-specific tartrate-resistant acid phosphatase 5 (TRAcP5) is significantly downregulated in biopsies isolated from osteosarcoma patients compared with nonmalignant bone tissue.…”
Section: Molecular Mechanisms Of Osteosarcoma Progressionmentioning
confidence: 99%